In situ simultaneous measurement system combining photoelastic, strain gauge measurement, and DIC methods for studying dynamic fracture. (December 2022) - Yue, Zhongwen; Wang, Xu; Peng, Linzhi; Xu, Shengnan; Ren, Meng
Highlights: Photoelastic method, DIC method and strain gauge method are used simultaneously. The stress field, displacement field and strain field are collected synchronously. The causes of errors in DSIFs obtained by three methods are discussed. Abstract: The photoelastic, digital image correlation (DIC), and strain gauge measurement methods are extensively used for studying dynamic fracture mechanics. However, few studies on dynamic fracture focus on combining these methods. In this study, a simultaneous measurement system for in situ investigation on dynamic fractures using the photoelastic, DIC, and strain gauge measurement methods was established for the first time. To reveal the performance of the system, impact experiments were conducted on three-point bending beam specimens fabricated using epoxy resin; consistent results were obtained from the three methods. The developed system provides rich experimental data, including full-field information of the stress, displacement, and strain fields.